EFFECT OF SUPPLEMENTATION OF DIFFERENT CAROTENOID SOURCES ON GROWTH AND COLOUR ENHANCEMENT OF KOI CARP (Cyprinus carpio) Fry - AND S. NANDA, D. CHOUDHURY, B. B. J. SAHOO , S. S. DAS (The Bioscan, 2018)
To know the effect of dietary supplementation of different carotenoides (marigold petal, rose petal, china rose petal and carrot) on growth and color enhancement, one hundred fifty number of koi carp (Cyprinus carpio) fry of average weight (0.63-0.75g) were distributed in five experimental groups and fed with five isonitrogenous diets such as T0 (control), T1 (15% marigold petal meal), T2 (15% rose petal meal), T3 (15% china rose petal meal) and T4 (15% carrot meal) for a period of 90 days. Significantly higher daily weight gain (0.03±0.001), weight gain % (425.12±32.01), SGR (0.794±0.019) and lower FCR (5.25±0.03) were observed in T3 group. Among the treatments maximum total carotenoid in the muscle was found in T3 group (17.791±0.395µg/g wet tissue) and the minimum was found in T0 group (4.782±0.412 µg/g wet tissue). The scores obtained in the panel test also showed highest value in T3 group (7.725±0.79). The computer assisted image analysis of the skin showed highest r (red) value in T3 group (0.454±0.024) and lowest in T0 group (0.320±0.017). Thus it is concluded that growth and color in koi carp fry can be enhanced using china rose petal meal at 15% level of inclusion in the diet.